Técnica de Angiotomografía Pulmonar para el Dignóstico de la Tromboembolia Pulmonar. - Sosa Barrera, Angel Ismael (2013)
The CT angiography is a relatively new procedure able to provide high resolution images of the vascular network, the adjacent bone and soft tissues. This present thesis work was performed with the aim to: Describe indications, procedures and limitations in performing pulmonary angiography as Protocol For Tromoembolismo, was performed at the Clinical Hospital San Agustin in the city of Loja, for which it has taken as sample 10 clinical cases, to carry out the same, during the period October 2012 to January 2013, leading to results that 20% of such cases are carried out by the presence of pulmonary embolism, between the ages of 35 to 80 years old. The methodology used was descriptive quantitative method for characterization, research and development of every single detail for the specification in a practical and descriptive of the important properties of the technical characteristics of pulmonary angiography. In conclusion Pulmonary angiography is feasible, optimal and appropriate that an assessment by 90% to observe pathological segments, demonstrates a high diagnostic power in detecting lung lesions, significant focusing on the detection of thrombi in the pulmonary vessels and included the subsegmentaciones. It is advisable to place the patient in a comfortable position, so that the same collaborate during the development of the exam in order to obtain quality images without distortion, verify urea and creatinine tests to proceed to completion of the same, as using non-ionic water-soluble contrast to avoid future complications realization. DESCRIPTION OR TAGS: Pulmonary Thromboembolism thrombi in pulmonary vessels Subsegmentaciones angiography water soluble contrast. DEGREE TO GET: RADIOLOGY TECHNOLOGIST DIAGNOSTIC AND IMAGE. ACADEMIC AREA: AREA OF HUMAN HEALTH. (TECHNICAL LEVEL TECHNOLOGY). CAREER: DIAGNOSTIC RADIOLOGY AND IMAGE.